KESUKSESAN PERDAGANGANBARANG ATAUPUN JASADALAM PANDANGAN Al-QUR’AN - Yuli Yani (Hijri, 2017)
In view of Islam trade has been in atus with sedimikian such, we are highly suggested to follow the teachings of Islam in any field, as well as in trade, many secrets if we trade in accordance with the teachings of Islam and follow the signs were limited by Islamic Shari'a , Many things can be done to improve the outcomes of our commerce with the Islamic way, such as always reading al- Fatihah when they wanted to trade, because in the sura contains a lot of implied meaning, such as the nature of Allah SWT. In the letter, namely ar-Rahman ar-Rahim. In the trade we also need to preserve the name of honesty because it will bring blessings to trade results. As well as we also have to ask for guidance and help of Allah SWT.